Increased Titin Compliance Reduced Length-Dependent Contraction and Slowed Cross-Bridge Kinetics in Skinned Myocardial Strips from Rbm20ΔRRM Mice - Pulcastro, Hannah C.; Awinda, Peter O.; Methawasin, Mei; Granzier, Henk; Dong, Wenji; Tanner, Bertrand C. W. (Frontiers in Physiology, 2016)
Titin is a giant protein spanning from the Z-disk to the M-band of the cardiac sarcomere. In the I-band titin acts as a molecular spring, contributing to passive mechanical characteristics of the myocardium throughout a heartbeat. RNA Binding Motif Protein 20 (RBM20) is required for normal titin splicing, and its absence or altered function leads to greater expression of a very large, more compliant N2BA titin isoform in Rbm20 homozygous mice (Rbm20ΔRRM) compared to wild-type mice (WT) that almost exclusively express the stiffer N2B titin isoform. Prior studies using Rbm20ΔRRM animals have shown that increased titin compliance compromises muscle ultrastructure and attenuates the Frank-Starling relationship. Although previous computational simulations of muscle contraction suggested that increasing compliance of the sarcomere slows the rate of tension development and prolongs cross-bridge attachment, none of the reported effects of Rbm20ΔRRM on myocardial function have been attributed to changes in cross-bridge cycling kinetics. To test the relationship between increased sarcomere compliance and cross-bridge kinetics, we used stochastic length-perturbation analysis in Ca2+-activated, skinned papillary muscle strips from Rbm20ΔRRM and WT mice. We found increasing titin compliance depressed maximal tension, decreased Ca2+-sensitivity of the tension-pCa relationship, and slowed myosin detachment rate in myocardium from Rbm20ΔRRM vs. WT mice. As sarcomere length increased from 1.9 to 2.2 µm, length-dependent activation of contraction was eliminated in the Rbm20ΔRRM myocardium, even though myosin MgADP release rate decreased ~20% to prolong strong cross-bridge binding at longer sarcomere length. These data suggest that increasing N2BA expression may alter cardiac performance in a length-dependent manner, showing greater deficits in tension production and slower cross-bridge kinetics at longer sarcomere length. This study also supports the idea that passive mechanical characteristics of the myocardium influence ensemble cross-bridge behavior and maintenance of tension generation throughout the sarcomere.